Therapeutic antibodies - Hale, Geoffrey (Henry Stewart Talks, 2020)
Why antibodies are so useful as drugs, Antibody therapy, The development of monoclonal antibodies, Genetic engineering, The problem of unwanted immunogenicity, The importance of affinity, Examples of antibodies for treatment of cancer, Examples of antibodies for treatment of immunological diseases